For.Dummies.IBM.Workplace.Services.Express.For.Dummies.Mar.2006 - Londergan, Stephen R. (Wiley Publishing, 2011)
This book captures two fundamental, important aspects of working with IBM Workplace Services Express. First are the technical considerations — the features, capabilities, customizations, and recommendations on how to use and personalize your IBM Workplace Services Express system. Then, this book goes on to provide insight into the business value and implications of applying this technology to your organization. You’ll see how capabilities in the product can improve your business processes, streamline your operations, provide better business control, and improve the collaboration and sharing of information for your team, workgroup, or organization.